PENGARUH PEMBERIAN PUPUK NPK MUTIARA DAN BANYAKNYA BIJI PER LUBANG TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH VARIETAS TASIA I (Arachis hypogaea L.) - Yustina S.K. Gulo; Robert G. Marpaung; Agnes I. Manurung (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
This study aims to obtain the correct dosage of NPK Mutiara fertilizer and the number of seeds per planting hole on the growth and production of peanut plants of Tasia 1. The research was conducted on Jl. Binjai km. 10.8, namely the Experimental Field of the Faculty of Agriculture, Darma Agung University, Sunggal Subdistrict, Deli Serdang Regency with a height of  28 m above sea level, starting from April to August 2020. This research method used a randomized block design (RAK). factorial consisting of two factors. The first factor is the dosage treatment of NPK Mutiara (N) fertilizer consisting of 4 levels, namely: N0 = 0 g / plot (0 kg / ha), N1 = 15 g / plot (100 kg / ha), N2 = 30 g / plot ( 200 kg / ha) and N3 = 45 g / plot (300 kg / ha). The second factor is the treatment of the number of seeds per planting hole (B) consisting of 3 levels, namely: B1 = 1 seed / planting hole, B2 = 2 seeds / planting hole and B3 = 3 seeds / planting hole. The results showed that the treatment of NPK Mutiara fertilizer up to 45 g / plot had a significant effect on plant height, number of main branches, flowering age, number of gynophores per plant, number of empty pods per plant, total number of pods per plant, pod weight per plot and weight of 100 seeds. Treatment of the number of seeds per planting hole had a significant effect on the number of main branches, flowering age, number of gynophores per plant, total number of pods per plant, pod weight per plot and weight of 100 seeds, but had no significant effect on plant height and number of pods. vacuum per plant. The combination treatment of NPK Mutiara fertilizer and the number of seeds per planting hole did not significantly affect the growth and production of peanuts.